Specificity of periphrase in the Song of the Songs translated by Methodius - Dyadyshcheva-Rosovetska, Juliya (Current issues of Ukrainian linguistics: theory and practice, 2025)
The article is dedicated to the specifics of periphrasis in the Methodian translation of the Song of Songs, a text of oral-poetic origin that has undergone literary processing. Its translation-adoptation peculiarities are emphasized: interlanguage, interconfessional, interethnic, and temporal as well. The importance of a comprehensive linguo-folkloristic analysis, carried out at all linguistic levels, when studying the poetics of the literary monument, is underscored. The author proposes to consider the article as preliminary observations that should precede further exhaustive and methodologically complex subsequent research. The definition of a periphrasis as a descriptive phrase where an object or phenomenon is not named directly but is presented through its attributes is proposed as a conclusion to the overview of the most mainstream contemporary studies, highlighting the range of issues related to periphrasis. The most representative periphrases in the text of the Song of Songs are considered and analyzed. Situational periphrases, pleonastic double periphrases that serve to express imagery, toponymic periphrases, periphrases that are metaphorical in nature, poetic periphrases based on visual ekphrasis, as well as gustatory, olfactory, etc. are differentiated. A construction based on the participial construction is highlighted, where the target word is "mother" or "beloved". Exquisite examples of composite periphrases for the referent word "fruits" are analyzed. The article also sets the base and explores possibilities for future research on Euphemistic paraphrases of taboo words. The consideration of periphrasis, which is widely represented in the Methodian devotional (chetiy) translation of the Song of Songs, is generalized as a technique of linguopoetics. It is emphasized that Methodius managed to deeply sense the specifics of periphrasis and find an adequate linguistic form for its implementation to familiarize readers with the stylistic richness of one of the most poetic books of the Bible.
Keywords: linguistics; Song of the Songs; linguo-poetics; linguo- stylistics; linguo-folkloristics